Self-Development as a Factor in the Professional Growth of Future Teachers - Ivaniuk, Hanna; Venhlovska, Olena; Antypin, Yevhen; Vovchok, Yaroslav (Journal of History Culture and Art Research, 2020)
The study aimed to substantiate the concept of "self-development as a factor in the professional growth of future teachers" and to empirically research the effectiveness of technological tools that affect the development of its components. Self-development as a factor in the professional growth of future teachers in the context of the article is considered as a motivated self-progress of applicants for higher education in pedagogical specialties, which is based on personal senses and aimed at developing their professional potential. To achieve this goal at different stages of the study, we applied: author questionnaires using Google service (Google Forms tool), individual protocols for self-assessment, diagnostic technologies of self-awareness and self-development - the flower of my research skills, a cascade of sequences, a basket of ideas, personal projects technologies - pedagogical portfolios, cases, Self-book, projects, business (imitation) games, maps of professional self-development. The generalization of the data of the empirical study took place using the methods of mathematical statistics – the Pearson's correlation coefficient using MS Excel (application of the "CORREL" function). The results of the study confirm the quantitative and qualitative indicators of the positive component dynamics of the formation of self-development for the professional growth of future teachers. It is proved that the use of a set of personal-projective tools contributes to the formation of professional self-development of the teacher, which is expressed by the components disclosed in the article. The application of our research: its results will help applicants for higher education (future teachers and lecturers of higher educational institutions of pedagogical specialties) consciously apply diagnostic, personal-projective technologies for the teacher’s self-development at the beginning of their activity. The study for the first time substantiates the essence of the concept and the components of self-development as a factor in the professional growth of future teachers; suggests a set of effective methods that have not been widely explained.